Niemcy na Ziemi Lubuskiej w latach 1945-1950 = Germans on Lubusz Land during the years 1945-1950 - Nowak-Małolepsza, Fatima (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The structure of national minorities on Lubusz Land became stable at the beginning of 1950s.That is why the period of 1945-1950 was the time in which the new society of this terrain had been shaping. This process was inextricably connected with the international policy regarding the changes of borders. As a result of political decisions, not only were the borders moved, bur the society structure of the Polish-German borderlands were also changed.
Keywords: Ziemia Lubuska; Niemcy (narodowość); historia; 1945-1950